KINDS OF FEMINISM IN RUPI KAUR SELECTED POEMS (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was to find out what kinds of feminism in Rupi Kaur selected poems. The method used in this study is descriptive qualitative research using a library research. The data sources for this study is Milk and Honey book by Rupi Kaur, articles and journals or websites that related in this study. The results of this study researcher found two kinds of feminism based on Abbot and Wallace’s theory; They are 9 data of Liberal Feminism and 3 poems of radical Feminism. In this research there are  7 poems contains kinds of feminism, In page 22,157,166,173 there are contains liberal feminism, and in page 16,27, and 28  there are contains radical feminism.